Analysis of Implementation of Entity Financial Accounting Standards Without Public Accountability for Inventories at PT. Kezies SPBU 142031142 - Natalia Br Karo Purba; M. Rizaldi Wibowo (International Journal of Economics (IJEC), 2022)
This study aims to analyze the application of financial accounting standards for entities without public accountability for inventories at PT. Kezies SPBU 142031142. This study uses a qualitative descriptive approach, aiming to find out whether the company's financial accounting standards are running well or not and to find out whether the inventory complies with the company's regulations. The subject of this research is PT. Kezies SPBU 142031142 and the object of this research are inventory reports and financial reports such as profit and loss and balance sheets of PT. This is because PT. Kezies SPBU 142031142 only presents the income statement as financial statement information. Based on the results of the analysis, it is also known that PT. Kezies SPBU 142031142 has not applied the Financial Accounting Standards for Entities Without Public Accountability for the reports of fuel oil inventories provided. This is because PT. Kezies SPBU 142031142 only presents inventory reports in a very simple way, namely only recording in the accounting book. As for the obstacles PT. Kezies SPBU 142031142 in applying the Financial Accounting Standards for Entities Without Public Accountability for inventories, namely the lack of knowledge of the owner. Kezies SPBU 142031142 feels that he is not yet professional in implementing SAK ETAP and the views of the owner of PT. Kezies SPBU 142031142 that the recording activities are carried out only to meet the needs of calculations and transparency so that it does not need to be done.